Матеріали для історії старшинського побуту на Слобідській Україні XVII – XVIII ст. (Козацька старшина у колі речей) - Маслійчук, В.Л. (My University, 2004)
V. Masliychuk. The Materials for a History of the Nobility's Everyday Life in the Sloboda Ukraine in XVII-XVIII centuries These are the publications of property and building descriptions. These materials are available for discovery of everyday life, economic interests and international contacts in the environment of the native ruling class (Cossack starshyna) in XVII-XVIII centuries.